Effects of Training for In-Hand Manipulation on Legibility of Urdu Handwriting - Jameel, Hafiz Tahir; Nabeel, Tanzila; Muhamamad Yaseen (JIE, 2023)
This research studied the effectiveness of training of In-Hand Manipulation on typically developing children to study the improvement in Urdu handwriting legibility of students of grade 4 and 5. Thirty nine participants with poor handwriting were taken from the general education schools. Pretest-Posttest Two Group Design was used in the study. Nineteen participants of experimental group were given training for the improvement of In-Hand Manipulation and 20 students from control group performed only routine school activities with no extra treatment. The results showed that overall legibility of experimental group was improved significantly as compared to control group (t = 5.49, p < 0.05). Overall readability (from -0.6 to 0.5), use of margin (from 0.5 to 0.8), shape of words (from 0.5 to 0.7), were improved components of legibility in experimental group. This study may be taken as a first step in the development of a tool for assessment of Urdu legibility in school setting.